Economics of grids, clouds, systems, and services : 8th International Workshop, GECON 2011, Paphos, Cyprus, December 5, 2011, Revised Selected Papers - Altmann, Jörn; Rana, Omer F.; Vanmechelen, Kurt (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed post-proceedings of the 8th International Workshop on Economics of Grids, Clouds, Systems, and Services, GECON 2011, held in Paphos, Cyprus, in December 2011. The 9 revised full papers presented together with 5 work in progress papers were carefully reviewed and selected from 27 papers. The papers are organized in topical sections on market mechanisms and negotiation; cost models, charging, and trading platforms; resource allocation, scheduling, and admission control; and two work in progress sections: risk assessment and economics of cloud services; and cost-aware adoption of cloud services.